2022
DOI: 10.3390/atmos14010079
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Long-Term ENSO, SST, and IOD Dynamics on Extreme Hydrological Events (EHEs) in the Kelani River Basin (KRB), Sri Lanka

Abstract: Hydrological extremes are common throughout the world and can be considered a globally significant phenomenon with severe environmental and social consequences. In recent decades, especially in the second half of the 20th century, Extreme Hydrological Events (EHEs) have attracted extensive attention. Physiological and anthropogenic factors have increased the frequency and severity of hydrological extremes worldwide in the last few decades. Recently, it has become a significant environmental issue in Sri Lanka.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Hydro-geomorphological events (namely, floods, debris flows, and landslides) affect urban environments worldwide, causing relevant disasters with increasing frequency and magnitude [1][2][3][4][5][6][7][8]. This is a direct consequence of two processes: climate change driven by the burning of fossil fuels in production systems [9][10][11] and uncontrolled or poorly planned urbanization in hazardous areas [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Hydro-geomorphological events (namely, floods, debris flows, and landslides) affect urban environments worldwide, causing relevant disasters with increasing frequency and magnitude [1][2][3][4][5][6][7][8]. This is a direct consequence of two processes: climate change driven by the burning of fossil fuels in production systems [9][10][11] and uncontrolled or poorly planned urbanization in hazardous areas [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of research has indicated that climate change has profound effects on agricultural production (Schlenker and Roberts, 2009). The rise in global average temperatures, changes in precipitation patterns, and an increase in the frequency and intensity of extreme weather events have all significantly affected agricultural production (Schlenker and Lobell, 2010;Lobell and Gourdji, 2012;Wijeratne et al, 2022;. Without effective measures in the coming decades, climate change poses a serious threat to crop yields, food security, and agricultural livelihoods (Challinor et al, 2014;Ray et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, precipitation is an important component of the global hydrological cycle. The United Nations Intergovernmental Panel on Climate Change (IPCC) in the Sixth Assessment Synthesis Report (IPCC, 2023) clearly pointed out that due to human activities and high-speed industrial development in recent years leading to a yearly increase in the concentration of greenhouse gases, the average global surface temperature increased by approximately 1.09 °C in just 10 years (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020), global warming will certainly accelerate the hydrological cycle, extreme precipitation events are bound to become more frequent (Adnan et al, 2022;Awais Naeem et al, 2022;Muhammad et al, 2022;Wijeratne Vithana et al, 2022;Abbas et al, 2023b;Waheed et al, 2023), and the average precipitation will increase slightly. With global warming, precipitation events are often prone to intensifying in some regions.…”
Section: Introductionmentioning
confidence: 99%